2013
DOI: 10.2337/db13-0663
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Reduces Reward-Driven Food Intake in Humans

Abstract: Experiments in animals suggest that the neuropeptide oxytocin acts as an anorexigenic signal in the central nervous control of food intake. In humans, however, research has almost exclusively focused on the involvement of oxytocin in the regulation of social behavior. We investigated the effect of intranasal oxytocin on ingestion and metabolic function in healthy men. Food intake in the fasted state was examined 45 min after neuropeptide administration, followed by the assessment of olfaction and reward-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
238
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(271 citation statements)
references
References 56 publications
23
238
8
2
Order By: Relevance
“…It has been observed that oxytocin reduced the intake of palatable foods, but was not able to modify food intake in the fasted state [10]. Accordingly, the lack of efficacy in reducing food intake observed in our study may be due to the energy-restricted diet received by participants.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…It has been observed that oxytocin reduced the intake of palatable foods, but was not able to modify food intake in the fasted state [10]. Accordingly, the lack of efficacy in reducing food intake observed in our study may be due to the energy-restricted diet received by participants.…”
Section: Discussioncontrasting
confidence: 49%
“…Preclinical studies indicate that oxytocin administration decreases food consumption and body weight in obese and lean animals [5] but the few clinical studies conducted to date have produced conflicting results [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin has also been linked to energy homeostasis mechanisms in animals, where it acts as a strong inhibitor of food intake and affects energy expenditure and glucose homeostasis [27][28][29][30][31]. Oxytocin has also been shown to play an important role in metabolism and energy balance in humans [32,33], such as reducing caloric intake with a preferential effect on fat intake [11] and reward-driven food intake in humans [34]. These findings are in line with our finding that reduced levels of delta oxytocin correlate with a high BMI in CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, animal studies and pilot experiments in humans have indicated that oxytocin might have a role in the regulation of eating behavior and metabolism in normal weight as well as with diet-induced obesity. Oxytocin administration in animals and humans inhibits food intake, increases energy expenditure, and reduces glucose levels (Morton et al 2012;Ott et al 2013;Lawson et al 2015). Interestingly, there are experiments, which suggest that the metabolic eff ects of oxytocin may be even enhanced in diet-induced obese in comparison to control weight (Th ienel et al 2016) with absent or minimal side eff ects.…”
Section: Th E Hypothalamus Role In the Food Intake Controlmentioning
confidence: 99%